An improved multi-objective topology optimization approach for tensegrity structures. Issue 1 (January 2018) - Xu, Xian; Wang, Yafeng; Luo, Yaozhi
This article presents an improved approach for topology optimization of tensegrity structures. The ground structure method is used to model the topology optimization problem of tensegrity structures into a mixed integer linear programming formulation. To improve the controllability of the found tensegrity structure, the nodes, besides the members, of the ground structure are treated as optimization variables, and direct and customized controls on the must-be-used nodes and on the number of struts connecting to each node are realized. A multi-objective function combining the previously used single objectives and a new developed single objective by weight coefficients is proposed to consider the multi-requirement on different aspects of tensegrity structures. Numerical examples are carried out to verify the proposed approach.